Human Capital Investment and Economic Growth in Saudi Arabia: Error Correction Model - Bokhari, Abla A.H. (International Journal of Economics and Financial Issues, 2017)
To examine the relationship between investment in human capital and economic growth in the Kingdom of Saudi Arabia for the period 1970-2014. Quantitative research design has been implemented. Granger Causality approach has been employed, followed by error correction model. The data stationarity and integration order have been tested, using the Augmented Dickey-Fuller. Any long-run or short-run causality was not observed between expenditure on education and economic growth (per capita GDP). 73.6% variation has been indicated by fixed capital formation of GNP, which is considered as an effective aspect. The results indicated that results are statistically significant with p-value (0.000) at 5% level of significance. Investment in human capital, with the right policy assessments and rehabilitation, can be translated into an essential element of growth in the Saudi economy. Keywords: Economic Growth, Human Capital, Error Correction model JEL Classifications: G0, G10, G38